Assessing the Lightweight Potential of Additively Manufactured Metals by Density-Specific Woehler and Shiozawa Diagrams - Merghany, Mohamed; Teschke, Mirko; Stern, Felix; Tenkamp, Jochen; Walther, Frank (Frontiers in Mechanical Engineering, 2022)
Additive manufacturing (AM) using the powder bed fusion (PBF) process is building up the components layer by layer, which enables the fabrication of arbitrary 3D-structures with unprecedented degrees of freedom. Due to the high cooling rates of the AM process, fine microstructures are generated. This leads to an improvement in quasistatic properties such as tensile strength, whereas the fatigue strength is comparable to conventionally manufactured metal or even reduced. This is due to the presence of process-induced defects formulated during the manufacturing process in combination with the increased notch stress sensitivity of high-strength metals. In this work, the fatigue damage assessment using different approaches like Murakami and Shiozawa for three AM alloys (AlSi10Mg, 316L, TNM-B1) containing defects is studied for better understanding for capability and mechanisms. Moreover, the effect of the lightweight potential is investigated, and how the specific material density can be considered when the fatigue damage tolerance is characterized.